Prevalence of overweight and obesity risk factors among adolescents in Tirupati schools and junior colleges - Gorantla, Anand Krishna; Bineni, Chandrasekhar (International Journal Of Community Medicine And Public Health, 2017)
Background: Obesity increases the risk of several chronic conditions including type 2 diabetes, cardiovascular diseases, gallbladder disease, osteoarthritis, back pain and some cancers. The present study was conducted to study the prevalence of obesity and overweight in adolescent population. Methods: A total of 1258 students (males-644; females-614) with an age group 10-19 years were selected from the higher secondary schools and junior colleges in the urban area of Tirupati. Results: The prevalence of overweight/obesity is found to be significantly higher in adolescents of private institutions than those from government institutions. Higher prevalence of overweight/obesity is found in school going adolescents 13.8% compared to college adolescents 6.7%. The variables like type of institution, residence, family history of obesity showed a significant positive association with overweight/obesity. Conclusions: The present study recommended that the private institutions should encourage healthy life style practices among students to prevent the risk of overweight/obesity from emergence.